Gut microbiota on anxiety and depression in primary Sjogren's syndrome: A novel insight - Ying Zhu; Kaiyuan Zhang; Ziyue Luo; Yu Song; Xinchang Wang (Heliyon)
Primary Sjogren's syndrome (pSS) is a prevalent disease in rheumatology and immunology. Anxiety, depression, and other mood disorders are pervasive across diverse sectors of society. Recent theories on the gut-brain axis have elucidated that the gut microbiota considered the second brain of humans, can modulate the central nervous system and behavior by mediating bidirectional response systems, including immunity, vagus nerve, and neuroendocrine pathways. This article reviews recent advancements that explore the mechanism between gut microbiota and emotional disorders in pSS. It aims to provide novel therapies for these emotional disorders in pSS.